ANALISIS USAHA PEDAGANG AYAM BROILER DI DESA TANJUNG ANOM KECAMATAN PANCUR BATU KABUPATEN DELI SERDANG - Sugeng Widodo; Media Agus Kurniawan (Bajang Institute, 2024)
This research aims to find out how much income is earned and determine the feasibility of selling broiler chickens in Tanjung Anom Village, Pancur Batu District. Respondents were all broiler chicken traders who sold in Tanjung Anom Village, Pancur Batu District, Deli Serdang Regency. The sampling method was carried out by census, the number of respondents was 6 broiler chicken traders. The analysis used in the research is Income Analysis and Business Feasibility Analysis. The results of the analysis show that the average amount of income earned by traders is IDR. 9,628,773/month. Business feasibility analysis obtained Broiler Chicken Sales Business Income of 1.19. This means that the business of selling broiler chickens in Tanjung Anom Village, Pancur Batu District is feasible because R/C > 1